Influence of B2O3 addition on the properties of TiO2 thick film at various annealing temperatures for hydrogen sensing - Mohd Chachuli, Siti Amaniah; Hamidon, Mohd Nizar; Ertugrul, Mehmet; Mamat @ Mat Nazir, Md. Shuhazlly; Jaafar, Haslina; Azis, Norhafiz (Springer, 2020)
To increase the adhesion of thick film on a substrate, boron oxide (B2O3) was added to titanium dioxide (TiO2), and the change in the morphology, crystallinity and band gap of TiO2 thick film was investigated. TiO2 and TiO2-B2O3 pastes were prepared and deposited on the microscopic glass using screen-printing technique and then annealed under air at different temperatures of 400°C, 450°C and 500°C for 30 min. The morphology, elemental composition, structure and absorption of the thick films were characterized using FESEM, EDX, XRD and UV–visible spectroscopy. The TiO2 and TiO2-B2O3 thick films were fabricated as gas sensors and exposed to 100–1000 ppm of hydrogen at an operating temperature of 300°C. The results revealed that the addition of B2O3 increased the crystallinity of anatase phases and rutile phases in TiO2 as annealing temperature increased. The TiO2-B2O3(T500) gas sensor exhibited the highest response to various concentrations of hydrogen (100–1000 ppm) at an operating temperature of 300°C.